Combatting the “fake one”: A case study of counterfeit Siti Khadijah Telekung. - Rosely, Nurhidayah; Abdullah Thani, Ayu Kamareenna; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim (Journal of Islamic, Social, Economics and Development, 2025)
Counterfeit goods purchase issues have become severe due to the tremendous consumer demand causing the mushrooming counterfeit markets. The dark markets pose the most substantial challenge for fashion manufacturers in preventing consumers from participating in counterfeiting activities as the growth of online marketplace enables the anonymous identity of both the seller and buyers. Based on the Siti Khadijah brand case study, this preliminary study sought to uncover insight into counterfeit goods purchased through the lens of fashion manufacturers through in-depth interviews. The data was analysed using inductive thematic analysis, and four themes emerged from this analysis: legal action, responsible consumers, unreachable audience, and lengthy process. The Siti Khadijah brand has taken serious measures to combat this illegal and unethical consumption practice. The conclusions confirmed that fashion manufacturers believe that educating and changing consumers' mindsets in respecting intellectual property rights were more sustainable prevention strategies than legal action and enforcement, which require many resources from fashion manufacturers. This preliminary study contributes knowledge to counterfeit branded fashion goods and consumer behaviour as the emerging themes described the insights captured from the Siti Khadijah brand, representing the Malaysian fashion industry, which has continuously become a victim of counterfeiters. This research contributes to scholarly and managerial knowledge in the Malaysian context through more cognizance of comprehending the actual cases of counterfeit consumption phenomena.